ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN YANG TERDAFTAR DI BEI - Suryani, Suryani; Natalia, Erni Yanti (LPPM Universitas Putera Batam, 2021)
Banks are very important for the economy of a country so that the performance of a bank to generate profitability is prioritized, the better the performance of a company, the higher the resulting profitability. The purpose of this study was to examine the effect of Capital Adequacy Ratio, Operating Income Operating Expenses, Loan Deposit Ratio on the profitability of banks listed on the IDX. This study uses secondary data with a company population of 43 banking companies listed on the IDX from 2016 to 2020 and the number of samples taken based on the purposive sampling method is 8 companies with total of 40 data. The data tested using the SPSS 20 program. The results of the test show that the Capital Adequacy Ratio has no significant effect on Return On Assets, so H0 is accepted and H1 is rejected, Operating Expenses Operating income and Loan Deposit Ratio has significant effects on Return on Assets, so H2 and H3 are accepted, H0 is rejected and Capital Adequacy Ratio, Operational Cost of Operating Income, Loan Deposit Ratio have a significant simultaneous effect on Return On Assets, so H4 is accepted, H0 is rejected.